Mending fences eaudiobook Deacon's family series, book 1. - Fisher, Suzanne Woods (Deacon's Family, 2019)
Every saint has a past. Every sinner has a future. Luke Schrock is a new and improved man after a stint in rehab, though everyone in Stoney Ridge only remembers the old Luke. They might have forgiven him, but nobody trusts him. Amos and Fern Lapp allow Luke to live at Windmill Farm under two conditions. First, Luke must make a sincere apology to each person he's hurt—a four-page, single-spaced list. Second, he must ask each victim of mischief to describe the damage he caused. Simple, Luke thinks. Offering apologies is easy. But discovering the lasting effects his careless actions have caused . . . that isn't so simple. It's gut-wrenching. And his list keeps growing. Izzy Miranda, beautiful and frustratingly aloof, also boards at Windmill Farm. Luke's clumsy efforts to befriend Izzy only insult and annoy her. Eager to impress, Luke sets out to prove himself to her by locating her mother. When he does, her identity sends shock waves through Stoney Ridge. Bestselling and award-winning author Suzanne Woods Fisher returns to her beloved Stoney Ridge for this brand-new series featuring some of her readers' favorite characters.